Resveratrol in Intestinal Health and Disease: Focusing on Intestinal Barrier - Wang, Youxia; Hong, Changming; Wu, Zebiao; Li, Shuwei; Xia, Yaoyao; Liang, Yuying; He, Xiaohua; Xiao, Xinyu; Tang, Wenjie (Frontiers in Nutrition, 2022)
The integrity of intestinal barrier determines intestinal homeostasis, which could be affected by various factors, like physical, chemical, and biological stimuli. Therefore, it is of considerable interest and importance to maintain intestinal barrier function. Fortunately, many plant polyphenols, including resveratrol, could affect the health of intestinal barrier. Resveratrol has many biological functions, such as antioxidant, anti-inflammation, anti-tumor, and anti-cardiovascular diseases. Accumulating studies have shown that resveratrol affects intestinal tight junction, microbial composition, and inflammation. In this review, we summarize the effects of resveratrol on intestinal barriers as well as the potential mechanisms (e.g., inhibiting the growth of pathogenic bacteria and fungi, regulating the expression of tight junction proteins, and increasing anti-inflammatory T cells while reducing pro-inflammatory T cells), and highlight the applications of resveratrol in ameliorating various intestinal diseases.